The procedural texts of the International Criminal Court - Kreß, Claus (Journal of international criminal justice, 2007)
With the recent approval of the Regulations of the Registry the procedural law applying before the International Criminal Court has been written down in the books almost completely. The following overview of the pertinent documents is to facilitate a thorough study of this new international criminal procedure, the architecture of which is of unprecedented complexity